An analysis of factors causing stunting in toddlers in the lahihuruk health center working area, west sumba regency - Boa, Grasiana Florida; Belarminus, Petrus; Saghu, Maria Mencyana P.; Widyastuti, Ririn; Bata, Verayanti A. (Institute of Computer Science (IOCS), 2025)
Stunting is a long-standing nutritional problem caused by low dietary intake over a long period due to inadequate feeding. Stunting can appear when a child is two years old or earlier. When a person grows up, stunting becomes one of the causes of their lack of productivity. It can also hinder economic growth increase poverty and widen inequality. Therefore, the nutritional intake of pregnant women, the lactation process, the adequacy of breast milk, complementary foods that contain enough nutrients, and how deworming is done for infants and toddlers should be reviewed from the beginning. These are thought to cause stunting. This study aims to determine the relationship between various factors that cause stunting in toddlers in the working area of the Lahihuruk Health Center, West Sumba Regency. This research was conducted in the Lahihuruk Community Health Center Working Area, West Sumba Regency, with a total sample of 60 stunting and healthy toddlers. The results showed that several factors cause stunting in toddlers, including maternal age, history of maternal illness during pregnancy, history of breastfeeding, complementary feeding, parenting history, environmental factors, and socioeconomic status. The results of chi-square analysis obtained a p-value of 0.000 where there is an association between these factors and the incidence of stunting in toddlers. It is hoped that health facilities can conduct home visits, provide additional food for stunted toddlers, and closely evaluate their development.